2021
DOI: 10.1021/acs.energyfuels.1c02261
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Development Characteristics of Coal under Organic Solvent Erosion and Its Nondestructive Testing Method

Abstract: The low permeability of coalbed methane (CBM) reservoirs restricts the efficient extraction of CBM. Organic solvent erosion is a sound method to improve the permeability of coal; however, a nondestructive testing (NDT) method for identifying the effects of erosion on coal is necessary. The ultrasonic characteristics of coal can reflect the physical state of coal; therefore, ultrasonic testing is a suitable method for identifying the erosion effect. First, the characteristics of fracture development in coal wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…20 The environmental impact of solvent extraction is inevitable. 21 The lowtemperature condition of liquid nitrogen freeze−thaw is difficult to achieve. 22 In recent years, research has shown that thermal stimulation technology can effectively reduce the adsorption capacity of CBM, increase the permeability, and thus promote the production of CBM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 The environmental impact of solvent extraction is inevitable. 21 The lowtemperature condition of liquid nitrogen freeze−thaw is difficult to achieve. 22 In recent years, research has shown that thermal stimulation technology can effectively reduce the adsorption capacity of CBM, increase the permeability, and thus promote the production of CBM.…”
Section: Introductionmentioning
confidence: 99%
“…Gas injection displacement has high energy consumption and low economic benefit, and it is only suitable for coal seams with high initial permeability . The environmental impact of solvent extraction is inevitable . The low-temperature condition of liquid nitrogen freeze–thaw is difficult to achieve …”
Section: Introductionmentioning
confidence: 99%
“…Ji et al 27 studied changes in the pore structure and adsorption capacity of coal after tetrahydrofuran (THF) extraction and found that the dissolution of small organic molecules reduced active groups, altered the pore space, and decreased the methane adsorption capacity. Lin et al 28 characterized the physical state of coal after organic solvent erosion using ultrasonic method and found that NMP and THF were the most effective in extracting the coal, and the crack width widening effect was obvious. Li et al 29 developed a coal molecular model to study methane adsorption and diffusion, finding that NMP treatment decreased methane adsorption by 41.6% and increased diffusion by 1.72 times.…”
Section: Introductionmentioning
confidence: 99%